ANALISIS KARAKTERISTIK NASABAH DALAM MEMPENGARUHI TINGKAT PENGEMBALIAN PINJAMAN (REPAYMENT RATE) KREDIT USAHA RAKYAT (KUR) MIKRO BRI (Studi pada PT Bank Rakyat Indonesia (Persero), Tbk Unit Wonorejo Cabang Lumajang) - Ovi Budi Widianto (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims  to show the effect of variable characteristics of the customer on the repayment rate of credit. The data used questionnaire is processed by using a Likert scale on each question item in a variable by using logistic regression analysis. The results showed that there is a simultaneous influence of the independent variable on the independent variable. And besides there are partial significant influence on the variables X1, X2, X3, and X5. The most dominant characteristic variables in influencing the loan repayment is operating income.Keyword: KUR Mikro, Reoayment Rate of Credit, Logistic Regression